Profitability and Technical Efficiencr of Irrigated Tomato Productinon in Some Selected Local Government Area of Niger State-Nigeria: Tomato Production - Enagi, I.M (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
The study assessed the profitability and technical efficiency of irrigated tomato production in Katcha, Bosso, and Wushishi Local Government Areas of Niger State, Nigeria. A sample of 122 tomato producers was selected through a multi-stage sampling method. Data were collected using structured questionnaires and analyzed using gross margin analysis, stochastic frontier function, and descriptive statistics employing a 4-point Likert scale. The total cost of production and total revenue in the study area was N226280.78 per hectare and N1053192.89 per hectare respectively. While the gross margin was 6.5%. Also, the mean technical efficiency of tomato farmers was 0.21 in the study area. Further findings revealed that the coefficient of education, farm size and extension visit had a significant relationship with tomato output. Tomato farmers in the study area encountered significant challenges, primarily the absence of storage facilities and the prohibitive cost of labor. Recommendations include providing training to farmers on post-harvest handling techniques to minimize losses and exploring alternative, cost-effective irrigation sources. Government intervention is crucial in facilitating access to such irrigation alternatives to alleviate financial burdens on farmers.